PERAN GENDER DALAM MENJELASKAN PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT BELI - Adi Suprapta Yasa, Bagus Made; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2015)
Changing attitudes dan behavior patterns of people in Denpasar are turning to the use of cosmetic products that are healthy dan environmentally friendly than chemical based products, lead to behavior change dan purchase intention. The purpose of this research was conducted to determine the influence of consumer attitudes dan subjective norms, dan to see the gender differences on the intention to buy green cosmetics brdan Oriflame in Denpasar. Data collection was performed using the non-probability sampling method in the form of purposive sampling. These results indicate that the regression models used have met the assumptions of classical test. This study concludes that each variable attitudes dan subjective norms positive dan significant effect on purchase intention, besides there are positive but not significant differences between consumer purchase intentions of women to men on purchase intention.
Keywords: Consumer Attitudes, Subjective Norms, Gender, Purchase Intention